High frequency transformer computer modeling - Abu-Siada, Ahmed; Islam, Syed (Curtin University of Technoklogy, 2007)
Frequency response analysis (FRA) technique is nowadays widely used in both factory and field applications as a diagnostic tool for power transformers. The main problem about FRA techniques is to interpret the observed evolution of the frequency response in order to identify failures. Transformer high frequency computer modeling is proposed in this work to be used with the FRA. The physical meaning of the model parameters allows the identification of the problem inside the transformer. The paper presents the model and experimental results and analysis of the frequency responses on the variations of the winding parameters. Effect of core, bushings, oil and tank on FRA is also investigated.